Study of disease pattern of patients admitted in Gynae & Obst. Department in a rural tertiary medical institute (KYAMC Journal, 2013)
The aim of this study was to find out the Gynaecological disease pattern, common diseases, age  distribution , organs involvement of female reproductive system, types of diseases etc. in admitted  patient of Khwaja Yunus Ali Medical College & Hospital (KYAMCH) a rural tertiary hospital in  Bangladesh. In this retrospective & descriptive study total 853 Gynaecological patients were  evaluated in 4 years period, who were admitted either from OPD or through emergency. Most of  the diagnosis were made after evaluation of organ involvement, 53% uterine origin, most are  benign 29%; 40% patient having normal menstrual cycle but suffering from Gynaecological  diseases like chronic cervicitis, lower abdominal pain(PID). Vaginal discharge, urinary tract  infection, ectopic pregnancy, different types of abortion. This study showed that the Gynaecological  disease pattern of Patients admitted in Obs& Gynae department of KYAMCH- a rural tertiary  medical institute.DOI: http://dx.doi.org/10.3329/kyamcj.v3i1.13656 KYAMC Journal Vol. 3, No.-1, June 2012 pp.220-222